Exosome-Laden Hydrogels: A Novel Cell-free Strategy for In-situ Bone Tissue Regeneration - Sun, Jinru; Yin, Zhifeng; Wang, Xiuhui; Su, Jiacan (Frontiers in Bioengineering and Biotechnology, 2022)
In-situ bone tissue regeneration, which harnesses cell external microenvironment and their regenerative potential to induce cell functions and bone reconstruction through some special properties of biomaterials, has been deeply developed. In which, hydrogel was widely applied due to its 3D network structure with high water absorption and mimicking native extracellular matrix (ECM). Additionally, exosomes can participate in a variety of physiological processes such as cell differentiation, angiogenesis and tissue repair. Therefore, a novel cell-free tissue engineering (TE) using exosome-laden hydrogels has been explored and developed for bone regeneration in recent years. However, related reviews in this field are limited. Therefore, we elaborated on the shortcomings of traditional bone tissue engineering, the challenges of exosome delivery and emphasized the advantages of exosome-laden hydrogels for in-situ bone tissue regeneration. The encapsulation strategies of hydrogel and exosomes are listed, and the research progress and future prospects of bioactive hydrogel composite system for continuous delivery of exosomes for in-situ bone repair is also discussed in this reviews.